Status Perkawinan Suami Istri Pasca Pembatalan Perkawinan Islam Di Indonesia - Sulkhan Zainuri (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2019)
the material law for the cancellation of Islamic marriages in Indonesia still requires further research considering there is a pluralism of regulations relating to it, namely Undang-undang no. 1 tahun 1974 concerning Marriage and Compilation of Islamic Law. This literature research study concludes that there is a dualism in terms of the termination of marriage in legislation, namely; the marriage is null and void and the marriage can be canceled so that it affects the legal status of husband and wife. However, due to the laws that are regulated remain the same, which is related to the status of children, property and third parties.